2016
DOI: 10.1016/j.trc.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A robust optimization approach for dynamic traffic signal control with emission considerations

Abstract: We consider an analytical signal control problem on a signalized network whose traffic flow dynamic is described by the Lighthill-Whitham-Richards (LWR) model (Lighthill and Whitham, 1955;Richards, 1956). This problem explicitly addresses traffic-derived emissions as side constraints. We seek to tackle this problem using a mixed integer mathematical programming approach. Such a class of problems, which we call LWR-Emission (LWR-E), has been analyzed before to certain extent. Since mixed integer programs are pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Consequently, the fourth class of methods are based on simulations and intelligent algorithms to enhance operations at signalized intersections by optimizing cycle length, green splits and offsets [28][29][30][31]. Methods based on simulation and heuristics are more realistic, robust, and efficient in capturing the non-linear and stochastic traffic conditions [32,33]. Various methods discussed above for traffic signal control were mainly focused on lane-based homogenous traffic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the fourth class of methods are based on simulations and intelligent algorithms to enhance operations at signalized intersections by optimizing cycle length, green splits and offsets [28][29][30][31]. Methods based on simulation and heuristics are more realistic, robust, and efficient in capturing the non-linear and stochastic traffic conditions [32,33]. Various methods discussed above for traffic signal control were mainly focused on lane-based homogenous traffic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results show a significant reduction of HC, NO x , CO and CO 2 emissions, in the range of [9 %, 14 %]. Other studies such as (Zhang et al 2009;Lv and Zhang 2012;De Coensel et al 2012;Han et al 2015) have confirmed the promising role traffic signal control have confirmed the promising role traffic signal control plays in reducing emissions.…”
Section: Introductionmentioning
confidence: 76%
“…Optimization of signal timing parameters using traffic microsimulation is a popular research topic. In one study, the authors have created an optimization model for signal timing (Han, Liu, Gayah, Friesz, & Yao, 2016). The authors of the study have considered fuel consumption as a criterion for optimizing signal timings.…”
Section: Literature Reviewmentioning
confidence: 99%